Peran Akuntan Syariah Di Era Disruption - Eny Latifah (Al-Musthofa: Journal of Sharia Economics, 2019)
The purpose of this study was to determine the role of sharia accontants in the era disruption, both in terms of their existence and contribution in the presentation of sharia and to maintain their code ethics in accordance with Islamic sharia. This reseach method uses a reseach method with a descriptive qualitative approach, where the date obtained is analyzed and then compared with the concepts obtained. The results of the study show that sharia accountants are able to maintain their axistence in the era disruption by improving technology skill while maintaining sharia principles and existing codes of athics.